Militancy in the Perspective of Industrial and Organizational Psychology - Endah Andriani Pratiwi; Shinta Febrina; Yoga Hardianto; Arief Budiarto (Journal La Sociale, 2024)
Resilience in the face of change, adversity and uncertainty is an attitude that illustrates the spirit of militancy. The research team observed that there is no standard concept of militancy and its application in organizational life. The terms militant and militancy are often interpreted negatively in Indonesia, as they are associated with radicalism and terrorism (Purwastuti, 2011). In fact, in the Big Indonesian Dictionary (KBBI), militant means "high spirited, passionate and hard-nosed", while militancy means "toughness in fighting (facing, difficulties, fighting, and so on)". The purpose of this research is to find formulations and develop concepts about militancy from the perspective of Industrial and Organizational Psychology, especially in human resource management. The benefits of this research are expected to emerge a steady concept of militancy from which a measuring instrument and intervention program can be developed to improve militant attitudes in industrial and organizational settings. The research approach used in this study is a qualitative approach with data collection methods, namely interviews. Respondents in this study are academics and practitioners who are involved in military psychology and practitioners in the field of Industrial and Organizational Psychology, especially in the field of human resource management (HRM). The results of this study are expected to be the basis for improving the quality of human resources in the organization through increasing the attitude of militancy in its human resources.